2021
DOI: 10.1002/nbm.4569
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium MRSI characterizations of glucose metabolism in orthotopic pancreatic cancer mouse models

Abstract: Detecting and mapping metabolism in tissues represents a major step in detecting, characterizing, treating and understanding cancers. Recently introduced deuterium metabolic imaging techniques could offer a noninvasive route for the metabolic imaging of animals and humans, based on using 2H magnetic resonance spectroscopic imaging (MRSI) to detect the uptake of deuterated glucose and the fate of its metabolic products. In this study, 2H6,6′‐glucose was administered to mice cohorts that had been orthotopically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…17 As a cancer imaging method, DMI has so far been tested in gliomas, EL4 (lymphoma cell line) models, 1,3 and now on PDAC. 18 Indeed, simulations, phantom, and in vivo comparisons confirm that higher SNR can arise from ME-bSSFP for DMI investigations, as compared to CSI. bSSFP had been used for spectroscopy within the context of hyperpolarized 13 C 40,43,44 and 31 P MRSI experiments 23 ; this study demonstrates that equal or larger gains could result for 2 H applications.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…17 As a cancer imaging method, DMI has so far been tested in gliomas, EL4 (lymphoma cell line) models, 1,3 and now on PDAC. 18 Indeed, simulations, phantom, and in vivo comparisons confirm that higher SNR can arise from ME-bSSFP for DMI investigations, as compared to CSI. bSSFP had been used for spectroscopy within the context of hyperpolarized 13 C 40,43,44 and 31 P MRSI experiments 23 ; this study demonstrates that equal or larger gains could result for 2 H applications.…”
Section: Resultsmentioning
confidence: 78%
“…For the LSL‐Kras G12D/+ ; LSL‐Trp53 R172H/+ ;Pdx‐1‐Cre (KPC)‐based pancreatic cancer model 16 examined in this study, 17 ongoing studies have shown that DMI can also highlight these tumors’ locations, via enhanced localized production of 2 H 3,3’ ‐lactate ca. 60 min after injection of a 2 H 6,6’ ‐glucose bolus 18 . By contrast, little or no lactate is evidenced outside the tumor’s location.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our studies indicate that [U-2 H]-pyruvate flux to lactate is mechanistically linked to the TERT-mediated increase in NADH in cell and in vivo tumor models. 2 H-MRS recently emerged as a novel method of imaging the metabolism of 2 H-labeled substrates in vivo and studies have largely focused on assessing 2 H-glucose metabolism in normal rat brain and in tumor-bearing animals 22,23,[25][26][27] . Importantly, De Feyter et al have established the clinical feasibility of using 2 Hglucose to monitor tumor burden in vivo in glioblastoma patients 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 H-MRS, in which the nuclear magnetic resonance of the 2 H moiety is interrogated, emerged as a versatile, innovative method of examining metabolic pathway activity in vivo 22 . Following administration of 2 H-labeled substrates such as glucose, acetate or fumarate, flux to metabolic products can be quantified in real-time in a noninvasive manner in preclinical tumor models in vivo [23][24][25][26][27] . Importantly, the feasibility of 2 H-MRS has been established in glioblastoma patients 23 , underscoring the clinical translatability of this method.…”
Section: Introductionmentioning
confidence: 99%